2020
DOI: 10.37294/jrkn.v4i1.214
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan Ibu Hamil Dengan Keinginan Ibu Hamil Dalam Memilih Metode Vaginal Birth After Caesarean (Vbac)

Abstract: ABSTRAK                                       Latar Belakang: ibu yang melahirkan dengan persalinan Sectio Caesarea (SC) terbukti secara bermakna meningkatkan kematian ibu. Risiko banyak terjadi pada persalinan SC yang direncanakan elektif(Villar, 2006). Beberapa tahun terakhir angka kejadian tindakan persalinan melalui SC meningkat melebihi target WHO. Upaya Vaginl Birth After Caesarean (VBAC) masih sedikit peminatnya (ACOG, 2010). Ibu yang takut menjalani proses persalinan secara normal disebabkan oleh banya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…To increase pregnant women's knowledge about VBAC delivery, medical personnel should provide complete information regarding the benefits, risks, and indications as well as criteria for implementing the VBAC method in order to achieve the desired success. According to research conducted by Diaris and Kusumaningsih (2020), the results were that there was a relationship between maternal knowledge and the mother's desire to choose a VBAC delivery method with a value of p=0.01, which means there was a relationship between knowledge and the mother's desire to choose a VBAC delivery method. Most mothers chose the repeated SC method, namely 71.0%, and only 29.6% chose the VBAC method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase pregnant women's knowledge about VBAC delivery, medical personnel should provide complete information regarding the benefits, risks, and indications as well as criteria for implementing the VBAC method in order to achieve the desired success. According to research conducted by Diaris and Kusumaningsih (2020), the results were that there was a relationship between maternal knowledge and the mother's desire to choose a VBAC delivery method with a value of p=0.01, which means there was a relationship between knowledge and the mother's desire to choose a VBAC delivery method. Most mothers chose the repeated SC method, namely 71.0%, and only 29.6% chose the VBAC method.…”
Section: Discussionmentioning
confidence: 99%
“…According to research conducted by Diaris & Kusumaningsih (2020), the results showed that there was a relationship between maternal knowledge and the mother's desire to choose a VBAC delivery method with a value of p=0.01, which means there was a relationship between knowledge and the mother's desire in choosing a VBAC delivery method. Most mothers chose the repeated SC method, namely 71.0%, and only 29.6% chose the VBAC method.…”
Section: Introductionmentioning
confidence: 99%